A report on the future of independent and scholarly publishing webinar by the Scholarly Kitchen. Issue 1 (13th January 2020) - Jones, Phill
Abstract : Key points The open access movement continues to gain pace, resulting in increasing regulatory requirements that constrain business models. Plan S itself may only have a modest immediate effect on industry‐wide sustainability but is the clearest indication of the 'direction of travel' for our industry yet. Recent negotiations between publishers and consortia represent a 'bigger deal' and may therefore lead to even greater economic power for large commercial publishers. Societies have a greater role than merely allowing researchers to get credit for and disseminate their work. A one‐size‐fits‐all model of open access may threaten the sustainability of other community services managed by learned societies. Do not panic about Plan S! Look to the needs of your community and offer a balanced portfolio of publications and services.